Optimized Placement for Embedded Radar and Communication Sensors in Wind Turbine Blades - Simon, Jonas; Moll, Jochen; Krozer, Viktor; Kurin, Thomas; Nuber, Andreas; Bagemiel, Oliver; Krause, Stefan; Issakov, Vadim (Structural Health Monitoring 2021: Enabling Next-Generation SHM for Cyber-Physical Systems - Proceedings of the 13th International Workshop on Structural Health Monitoring, IWSHM 2021, 2021)
The present work describes the simulation procedure to determine an optimal sensor placement for RadCom (radar and communication) sensors operating in the frequency band from 57-63 GHz inside a wind turbine blade. Optimal placement means a full penetration and coverage of the blade as well as a communication path from every node to the blade’s root can be achieved. Furthermore, triple coverage is necessary to allow the localization of structural changes in the blade and its surface, such as ice aggretion. The sensors are partly applied to the surface and partly embedded in the core material of the rotor blade. In this way the blade can be monitored during the entire operation for structural health monitoring (SHM) purposes. The simulations take into account the transmission of waves, refraction, dispersion in the material and are based on material data obtained from measurements of rotor blade materials, as well as antenna data. The resulting sensor distribution is the basis for a prototype design of a 30 m long blade with embedded sensors for full-scale SHM testing. Since embedded sensors are not accessible after completion of the manufacturing process, the simulation results are key to the experiments success.
CRIS-Team Scopus Importer:2024-12-16